The Influence of Milling Ball Size on the Structural, Morphological and Catalytic Properties of Magnetite (Fe3O4) Nanoparticles toward Methylene Blue Degradation. (October 2020) - Amiruddin, Erwin; Awaluddin, Amir; Hariani, Innike; Sihombing, Ribka; Angraini, Riska
Abstract: Structural, morphological properties and the catalytic activity of magnetite (Fe3 O4 ) nanoparticles for degradation of methylene blue have been studied. The magnetite nanoparticles were synthesised from Padang beach sand West Sumatera by 2 steps ball milling method. Structures and morphologies of the synthesized magnetite nanoparticles were investigated using X-ray diffraction (XRD) and scanning electron microscopy (SEM). It was shown that the particle size of the magnetite nanoparticles can be controlled by milling ball size. The average grain size of magnetite particles milled for milling ball size of 0.7 cm and 1.5 cm was found to be 81.25 nm and 30.75 nm, respectively. Scanning electron microscopy (SEM) images show that the particle size of samples decreases as milling ball size increases and the grains exhibit irregular form. The effect of milling ball size on the degradation efficiency of catalytic reaction exhibited a good ability to degrade methylene blue from aqueous solutions with a maximum methylene blue removal rate of 86.79% for 10 hours reaction time.